Optogenetic Light Sensors in Human Retinal Organoids - Garita-Hernandez, Marcela; Guibbal, Laure; Toualbi, Lyes; Routet, Fiona; Chaffiol, Antoine; Winckler, Celine; Harinquet, Marylin; Robert, Camille; Fouquet, Stephane; Bellow, Sebastien; Sahel, José-Alain; Goureau, Olivier; et al. (Frontiers in Neuroscience, 2018)
Optogenetic technologies paved the way to dissect complex neural circuits and monitor neural activity using light in animals. In retinal disease, optogenetics has been used as a therapeutic modality to reanimate the retina after the loss of photoreceptor outer segments. However, it is not clear today which ones of the great diversity of microbial opsins are best suited for therapeutic applications in human retinas as cell lines, primary cell cultures and animal models do not predict expression patterns of microbial opsins in human retinal cells. Therefore, we sought to generate retinal organoids derived from human induced pluripotent stem cells (hiPSCs) as a screening tool to explore the membrane trafficking efficacy of some recently described microbial opsins. We tested both depolarizing and hyperpolarizing microbial opsins including CatCh, ChrimsonR, ReaChR, eNpHR 2.0 and Jaws. The membrane localization of eNpHR 2.0, ReaChR and Jaws was the highest, likely due to their additional ER release and membrane trafficking signals. In the case of opsins that were not engineered to improve trafficking efficiency in mammalian cells such as CatCh and ChrimsonR, membrane localization was less efficient. Protein accumulation in organelles such as Endoplasmic Reticulum (ER) and Golgi was observed at high doses with CatCh and ER retention lead to an unfolded protein response. Also, cytoplasmic localization was observed at high doses of ChrimsonR. Our results collectively suggest that retinal organoids derived from hiPSCs can be used to predict the subcellular fate of optogenetic proteins in a human retinal context. Such organoids are also versatile tools to validate other gene therapy products and drug molecules.